Neutron scattering study of the layered Ising magnet CsDy(MoO4)2 - Khatsko, E.N.; Zheludev*, A.; Tranquada, J.M.; Klooster**, W.T.; Knigavko, A.M.; Srivastava, R.C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The quasi-two-dimensional antiferromagnet CsDy(MoO4)2 is studied by neutron diffraction and quasielastic neutron scattering. The crystal structure of two low-temperature phases (below 120 K and below 40 K) is determined. An approximate structure of the magnetically ordered phase (TN = 136 . K) is proposed. In the ordered state the order-parameter critical exponent b = 0.17(0.01), the in-plane correlation length exponent n = 0.94 (0.07), and the staggered susceptibility critical index g = 1.01 (0.04) were determined. Comparing these results to the exact solution for a 2D Ising magnet we conclude that, although 2D behavior is apparent in CsDy(MoO4)2, there are deviationsfrom the simple 2D Ising model.